PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN PADA RUMAH SAKIT KHUSUS GIGI DAN MULUT KOTA BANDUNG - Heni Rohaeni; Irna Rahayu (Jurnal Administrasi Publik, 2017)
The hospitals as a health service provider should already know how the quality of they service can be provide satisfaction to the patient. This study is aims to analyze the effect of service quality on patient satisfaction at Rumah Sakit Khusus Gigi dan Mulut Kota Bandung. Population in this study is patient of RSKGM Kota Bandung with total sample 99 respondent. Data collection was done by distributing questionnaires with non-probability sampling technique. Data analysis technique is used coefficient correlation test, coefficient determination test and linear regression test to know how far the relationship and effect of service quality to patient satisfaction at RSKGM Kota Bandung. The result of analysis correlation test indicate that service quality variable have value r equal to 0,785 is in range 0,60-0,79 or in category strong relation. The result of determination test or Adjusted R Square is 0,616. This means that 61,62% of consumer satisfaction can be explained by service quality variables, while the rest is explained by other variables which not examined in this study.